∫ 0 ∞ ( x + 1 ) 7 x 4 ln ( x + 1 ) d x
If the integral above is equal to q p , where p and q are coprime positive integers, find p + q .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Awesome substitution! Just a fantastic one !!
Using the beta function B ( a , b ) = ∫ 0 ∞ ( 1 + x ) a + b x a − 1 d x we see that ∫ 0 ∞ ( 1 + x ) 7 x 4 ln ( 1 + x ) d x = − ∂ b ∂ B ( 5 , 2 ) = Γ ( a + b ) Γ ( a ) [ ψ ( a + b ) − ψ ( b ) ] ∣ ∣ ∣ ∣ ( a , b ) = ( 5 , 2 ) which is equal to Γ ( 7 ) Γ ( 5 ) [ ψ ( 7 ) − ψ ( 2 ) ] = 3 0 1 [ 2 1 + 3 1 + 4 1 + 5 1 + 6 1 ] = 6 0 0 2 9 making the answer 6 2 9 .
Excellent !
We could simply substitute ln(x+1)=t . then rearrange to get t.(e^t -1)^4/e^6t. . then use by parts taking t as differentiable function
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 ∞ ( x + 1 ) 7 x 4 ln ( x + 1 ) d x Let u = x + 1 1 ⟹ x = u 1 − 1 = u 1 − u ⟹ d x = − u 2 1 d u = ∫ 1 0 ( u 1 − u ) 4 − u 2 ( − ln u ) u 7 d u = ∫ 1 0 ( u − 1 ) 4 u ln u d u By integration by parts: f ′ = ( u − 1 ) 4 u , g = ln u = ( 6 u 6 − 5 4 u 5 + 2 3 u 4 − 3 4 u 3 + 2 u 2 ) ln u ∣ ∣ ∣ ∣ 1 0 − ∫ 1 0 ( 6 u 5 − 5 4 u 4 + 2 3 u 3 − 3 4 u 2 + 2 u ) d u = 0 + 3 6 u 6 − 2 5 4 u 5 + 8 3 u 4 − 9 4 u 3 + 4 u 2 ∣ ∣ ∣ ∣ 0 1 = 3 6 1 − 2 5 4 + 8 3 − 9 4 + 4 1 = 6 0 0 2 9
⟹ p + q = 6 2 9